Geothermal Exploration in the Burwash Landing Region, Canada, Using Three-Dimensional Inversion of Passive Electromagnetic Data - Victoria Tschirhart; Maurice Colpron; James Craven; Fateme Hormozzade Ghalati; Randy J. Enkin; Stephen E. Grasby (Remote Sensing, 2022)
Sustainable development of Canada’s North requires an increased focus on renewable, zero-emission energy sources. Burwash Landing in Yukon is prospective for geothermal energy based on a high geothermal gradient, local occurrence of warm groundwater and proximity to the active, crustal-scale Denali fault. Uncertainties about the potential geothermal system include the nature and geometry of fluid pathways, and heat sources required to drive a hydrothermal system. In this study, we inverted three passive electromagnetic datasets—321 extremely low frequency electromagnetic, 33 audiomagnetotelluric and 51 magnetotelluric stations—to map the subsurface electrical structure to 8 km depth. Our new model reveals vertical conductive structures associated with the two main faults, Denali and Bock’s Creek, which we interpret to represent fluid-deposited graphite and hydrothermal alteration, respectively. Our model supports an interpreted releasing bend on the main Denali fault strand. This is associated with the deepest conductivity anomaly along the fault and potential for deeper penetration of fluids. Enigmatic conductive bodies from 1 to > 6 km depth are associated with intermediate to mafic intrusions. Fluids released from these bodies may advect heat and provide a possible heat source to mobilize hot fluids and sustain a geothermal system in the region.